Impacts national policies on indigenous people livelihood in Nepal: A case study of the Raute community - BANU YASIN; KENICHI MATSUI (Journal of Advanced Research in Social Sciences and Humanities, 2019)
Aim: The primary purpose of this research was to analyze and evaluate the policies currently in place in Nepal that affect Nepal’s indigenous population. This paper focuses on the Raute people and how government decisions have impacted their standard of living.Method: This study used a descriptive methodology. The Raute people of Nepal’s mid to far-western development regions were singled out because they seem to have felt the greatest impact from shifting international legal norms and domestic policy agendas.Findings: Evidence from various regions, such as Africa, Latin America, and Asia, shows that national policies often need to give more priority to protecting indigenous peoples and their knowledge. Adivasi Janajati, Nepal’s indigenous people, account for about 37.2% of the country’s total population. They comprise a sizable population but have been marginalized from mainstream society. The dominant groups have effectively marginalized Indigenous peoples’ autonomy in terms of territory, resources, language, culture, customary law, and access to political and economic power.Implications/Novel Contribution: Even though Nepal has ratified ILO Convention No. 169 on Indigenous and Tribal Peoples, the rights of indigenous people are not guaranteed in the country’s recently promulgated Constitution of 2015. How this brand-new constitution and national laws deal with the provisions of this ILO Convention remains to be seen.